Factors influencing the resocialization of migrant older adults in China: a cross-sectional study - Cao, Meijuan; Wang, Yating; Liu, Huiping; Li, Qiang (Frontiers in Public Health, 2025)
BackgroundIn the context of the further expansion of the aging population and the scale of migration, the issue of resocialization of migrant older adults has attracting attention due to its close association with their physical and mental health. This study aimed to identify the status and influencing factors of resocialization among migrant older adults under the guidance of the Social ecosystem theory framework.MethodsA cross-sectional study was conducted with a convenience sample of 977 migrant older adults from Hangzhou, China. The Chinese version of the Resocialization Scale was used to evaluate the resocialization degree of migrant older adults.ResultsThe total resocialization score of migrant older adults was 74.21 ± 9.08, with a range of 67.71–86.32% for each dimension, indicating that there is still significant room for improvement in the resocialization level of migrant older adults. Multiple linear regression analysis showed that age, education, monthly income, household registration, support from adult children, personality characteristics, resocialization willingness, satisfaction with the medical insurance system, satisfaction with the regional policies regarding older adults, and satisfaction with community construction were significantly associated with the level of resocialization.ConclusionCommunity workers should develop individualized intervention plans according to the different circumstances of migrant older adults, integrate the strengths of Government, society, and the family, improve their ability to reintegrate into society, guide and support them, and promote their reasonable resocialization.